Simulation Research of Simplified Dynamic Matrix Control. Issue 1 (1st October 2022) - Zhang, Deli; Wang, Na; Pang, Chunfeng; Zhu, Longfei
ABSTRACT: Aiming at the shortcomings of matrix inversion and large amount of calculation in dynamic matrix control, a simplified algorithm is proposed. The algorithm introduces the expected attenuation factor of control increment to make the control increment gradually close to zero in the control time domain. In this way, the matrix inversion in the algorithm is simplified to pure value inversion (i.e. taking the reciprocal), which greatly reduces the amount of calculation, improves the calculation efficiency and reduces the adjustment of control parameters. Therefore, the real-time performance of the algorithm is strong, It is convenient for microcomputer programming. The simulation results show that the improved DMC algorithm is due to the improved DMC Algorithm in ensuring the real-time performance and the dynamic performance of the controlled object.